2008
DOI: 10.1111/j.1475-6811.2008.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization and assessment of disengagement in romantic relationships

Abstract: Research examining relationship distress and dissolution highlights the importance of romantic disengagement. However, prior conceptualizations and measures of romantic disengagement have tended to combine disengagement with related but distinct constructs hindering the study of romantic disengagement. In the present study we conducted exploratory factor analyses to demonstrate that disengagement is a relatively distinct construct and to clarify the conceptualization of romantic disengagement. More importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…Women who engage in IPV are more likely to experience depressive symptoms and low selfesteem (e.g., Kim & Capaldi, 2004;Whiting, Simmons, Havens, Smith, & Oka, 2009); trauma-related symptoms resulting from past experiences of abuse and neglect (e.g., Chen & White, 2004;Flemke & Allen, 2009;Miller & Meloy, 2006;White & Widom, 2003); conduct problems and antisocial behavior (e.g., Huesmann, Dubow, & Boxer, 2009;Kim & Capaldi, 2004); personality traits such as aggressiveness, impulsivity, or neuroticism (e.g., Barry, Lawrence, & Langer, 2008;Bettencourt, Talley, Benjamin, & Valentine, 2006); and borderline or antisocial personality disorders (e.g., Clift & Dutton, 2011). Depression and low self-esteem, in particular, appear to be stronger correlates of women's IPV perpetration than men's (Capaldi et al, 2012).…”
Section: Distal Correlates Of Women's Intimate Partner Violencementioning
confidence: 99%
“…Women who engage in IPV are more likely to experience depressive symptoms and low selfesteem (e.g., Kim & Capaldi, 2004;Whiting, Simmons, Havens, Smith, & Oka, 2009); trauma-related symptoms resulting from past experiences of abuse and neglect (e.g., Chen & White, 2004;Flemke & Allen, 2009;Miller & Meloy, 2006;White & Widom, 2003); conduct problems and antisocial behavior (e.g., Huesmann, Dubow, & Boxer, 2009;Kim & Capaldi, 2004); personality traits such as aggressiveness, impulsivity, or neuroticism (e.g., Barry, Lawrence, & Langer, 2008;Bettencourt, Talley, Benjamin, & Valentine, 2006); and borderline or antisocial personality disorders (e.g., Clift & Dutton, 2011). Depression and low self-esteem, in particular, appear to be stronger correlates of women's IPV perpetration than men's (Capaldi et al, 2012).…”
Section: Distal Correlates Of Women's Intimate Partner Violencementioning
confidence: 99%
“…) • Structured Diagnostic Interview for Marital Distress and Partner Aggression: Heyman et al (2001) Conflict management/problem-solving skills: • Marital Satisfaction Inventory-Revised a : Snyder and Aikman (1999) • Communication Skills Test (CST): Floyd (2004) • 10-minute problem solving interaction task coded for positive and negative behaviors and/or affect b : Specific Affect Coding System; Shapiro and Gottman (2004); Rapid Marital Interaction Coding System; Heyman (2004) • Areas of Change Questionnaire: Weiss and Birchler (1975) Interpartner support skills : • Support in Romantic Relationships Scale (SIRRS): Dehle, Larsen, and Landers (2001) • 10-minute social support interaction task coded for positive and negative support provision and solicitation behaviors b : Social Support Interaction Coding System; Pasch, Harris, Sullivan, & Bradbury (2004); Support Behavior Code; Suhr, Cutrona, Krebs, & Jensen (2004)Emotional intimacy/disengagement: • Romantic Disengagement Scale (RDS):Barry, Lawrence, and Langer (2008) Forgiveness:• Dispositional forgiveness:Fincham and Beach (2002) • Event forgiveness:Fincham, Beach, and Davila (2004) Commitment :• Commitment Inventory:Stanley and Markman (1992) Psychological, emotional, and physical aggression:•Mulitidimensional Emotional Abuse Scale: Murphy and Hoover (1999) • Conflict Tactics Scales -2nd Version: Physical Assault Scale and Injury and Consequences Scale a : Straus, Hamby, Boney-McCoy, and Sugarman (1996) • Structured Diagnostic Interview for Marital Distress and Partner Aggression: Heyman, Feldbau-Kohn, Ehrensaft, Langhinrichsen-Rohling, and O'Leary (2001)…”
mentioning
confidence: 99%
“…Although discussing these components separately aids in description, factor analyses suggest that disengagement comprises a single broad factor in which these four components are included (Barry et al, 2008). Therefore, in the present paper, I conceptualize disengagement as a single construct that includes emotional, affective, cognitive, and behavioral components.…”
Section: Conceptualizing Romantic Disengagementmentioning
confidence: 96%
“…Snyder and Regts (1979) conducted factor analyses of 127 items assessing global marital distress and found two factors: one representing marital conflict (which they termed -disharmony‖) and one representing romantic disengagement (which they termed -disaffection‖). Similarly, in the process of creating a measure of romantic disengagement, Barry, Lawrence, and Langer (2008) found that romantic disengagement formed a factor separate (albeit related) from negative affect. In sum, there is converging evidence from both factor analytic and basic research studies that romantic disengagement represents a stage of marital decline that is relatively unique from high levels of marital conflict.…”
mentioning
confidence: 99%
See 1 more Smart Citation